Beta vulgaris L. var. cicla improves memory deficits in intracerebroventricular streptozotocin injected rats: Role on neuroinflammation - ERTAŞ, BÜŞRA; GÜLHAN, REZZAN (MARMARA UNIV, 2021)
Alzheimer's disease is a challenging disease for patients due to progressive loss of cognition and behavioral disorders. Disruption of cholinergic transmission and neuroinflammation are the most important mechanisms underlying cognitive damage. Beta vulgaris L. var. cicla (BV) has been reported to have various pharmacological effects associated with its rich antioxidant content. In addition, anti-cholinesterase and antiinflammatory activities of BV have been demonstrated in vitro. The aim of this study is to elucidate the therapeutic effect of BV against cognitive impairment, reduction in cholinergic transmission and neuroinflammation caused by intracerebroventricular (ICV) administration of streptozotocin (STZ). STZ was administered bilaterally at a dose of 3 mg/kg via ICV to rats, and BV treatment at a dose of 2 g/kg for 21 days was administered orally to STZ-induced animals. After behavioral tests, AChE activity, TNF-alpha and IL-1 beta levels were measured in hippocampus and cortex tissues excised from decapitated animals. Novel object recognition and passive avoidance test showed that the treatment of BV reverted the ICV-STZ induced memory dysfunctions in rats. Furthermore, increased AChE levels in the hippocampal and cortical tissues of STZ-induced rats were significantly reduced with 21 days of BV treatment. In conclusion, these results confirm that STZ administration caused cholinergic hypofunction, neuronal inflammation and cognitive dysfunction in rats, and BV therapy significantly inhibited these changes with its potential neuroprotective activity.
Keywords: Alzheimer's disease; Beta vulgaris L. var. cicla; cholinergic dysfunction; neuroinflammation; cognitive function; OXIDATIVE STRESS; ALZHEIMERS-DISEASE; EXTRACT; CHOLINESTERASE